Influence of snow on near-surface ground temperatures in upland and alluvial environments of the outer Mackenzie Delta, northwest territories - Morse, P.D.; Burn, C. (Christopher R.); Kokelj, S.V. (Canadian Journal of Earth Sciences, 2012)
Relations between snow cover, active-layer thickness, and near-surface ground temperatures were determined in 2005-2009 for a diverse range of alluvial and upland settings in the outer Mackenzie Delta. Here, the snow cover developed primarily by wind redistribution, with its spatial variation controlled by topography in uplands and vegetation height in alluvial lowlands. Snow cover was the primary influence on freeze-back duration and the mean annual temperature at the top of permafrost (TTOP), with the difference in median TTOP between alluvial (-3.7 °C) and upland (-6.1 °C) settings related to the greater snow depth and soil moisture in the alluvial plain. The active layer was generally deeper in the wet alluvial lowlands, where the average duration of active-layer freeze back (101 days) was nearly double the time taken in the well-drained uplands (55 days). The surface offset (ΔT S; up to 11 °C) dominated the difference between annual mean air temperature (AMAT) and TTOP (ΔT). In alluvial terrain, ΔT S varied with snow depth, but in the uplands, ΔT S was more consistent from site to site. The small thermal offset (<2 °C) was slightly greater in alluvial terrain than in the uplands. The overall range in ΔT (2-10 °C) led to a range during the study of 7.2 °C in TTOP at the sites. The range in AMAT was 1.3 °C but up to 1.7 °C in TTOP at any one site. Permafrost was well established throughout the area except adjacent to channels where TTOP was close to 0 °C.